Cyber Crime From Social Media Against Acts Of Terrorism In Papua - Sunaryo Mad Arab; I.B. Putra Jandhana; Ade Muhammad; Muhammad Ihsan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
On various social media platforms, including Instagram in Indonesia, hate speech is often found. This phenomenon can lead to various online criminal acts or Cyber Crime, such as harassment, stalking, doxxing, and solicitation of violence. Armed Criminal Groups (KKB) also use the internet and social media as part of their struggle, so this form of cyber crime can be at risk of developing into cyber warfare. Regulation of the Chief of National Police No: SE/6/X/2015 states that hate speech includes insults, defamation, blasphemy, provocation, incitement, or the spread of fake news. Social media is also a source of news about hoaxes and racial discrimination against Papuans and non-Papuans. This can be used by the KKB to spread hoaxes and justify the acts of violence they committed against indigenous Papuans (OAP) and non-Papuans who were victims in the conflict.